Perkembangan Kompetensi Pedagogik Guru Kelas Di Sekolah Dasar: Analisis Survei - Mardicko, Afri; Fatahillah, Fatahillah; Pangestu, Amanda Kurnia (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
This research aims to analyze the level of pedagogical competence of class teachers in elementary schools (SD) in Pagelaran District, Pringsewu Regency, Lampung. Teacher pedagogical competence is a key factor in improving the quality of learning and student learning outcomes. However, based on initial observations, it was found that the average teacher's pedagogical competence was still relatively low. Gaps in the mastery of pedagogical competencies, especially in rural areas, have not been studied much through empirical data-based survey approaches. The research method used is descriptive quantitative with a survey approach. The sample consisted of 50 class teachers selected using cluster sampling techniques from 15 state elementary schools. Data was collected through a Guttman scale questionnaire and analyzed descriptively, with validity and reliability tests to ensure the quality of the instrument. The research results show that the majority of teachers have high pedagogical competence, especially in understanding student characteristics (95%), mastering learning theory (94%), and being able to develop a curriculum (92%). Overall, 96% of teachers fell into the "very high" category and 4% in the "high" category. The contribution of this research provides empirical data that is useful for local governments and educational institutions in designing policies to increase teacher competency. Further research with a broader scope is needed to strengthen these findings. However, this study has limitations in covering the area and limited sample size, so generalization of the results must be done with caution. Keywords: Pedagogical competence; class teacher; primary school; quality of learning Abstrak Penelitian ini bertujuan melihat perkembangan terbaru kompetensi Pedagogik Guru SD yang ada di Kec. Pagelaran, Kab. Pringsewu, Lampung. Kompetensi pedagogik guru merupakan faktor kunci dalam meningkatkan kualitas pembelajaran dan hasil belajar siswa. Namun berdasarkan observasi awal ditemukan bahwa rata-rata kompetensi pedagogik guru masih tergolong rendah. Selain itu kesenjangan dalam penguasaan kompetensi pedagogik, terutama di daerah pedesaan masih belum banyak dikaji melalui pendekatan survei berbasis data empiris. Metode penelitian yang digunakan adalah kuantitatif deskriptif dengan pendekatan survei. Sampel terdiri dari 50 guru kelas yang dipilih menggunakan teknik cluster sampling dari 15 SD Negeri. Data dikumpulkan melalui angket skala Guttman dan dianalisis secara deskriptif, dengan uji validitas dan reliabilitas untuk memastikan kualitas instrumen. Hasil penelitian menunjukkan bahwa sebagian besar guru memiliki kompetensi pedagogik tinggi, terutama dalam memahami karakteristik siswa (95%), menguasai teori pembelajaran (94%), serta mampu mengembangkan kurikulum (92%). Secara keseluruhan, 96% guru masuk dalam kategori "sangat tinggi" dan 4% dalam kategori "tinggi". Kontribusi penelitian ini memberikan data empiris yang bermanfaat bagi pemerintah daerah dan institusi pendidikan dalam merancang kebijakan peningkatan kompetensi guru. Penelitian lebih lanjut dengan cakupan yang lebih luas diperlukan untuk memperkuat temuan ini. Namun, penelitian ini memiliki keterbatasan dalam cakupan wilayah dan jumlah sampel yang terbatas, sehingga generalisasi hasil harus dilakukan dengan hati-hati. Kata kunci: Kompetensi Pedagogik; guru kelas; Sekolah Dasar; kualitas pembelajaran